The Impact Of China – Emission Trading System Policy Effectiveness on Economic and Future Forecast: Evidence From Pilot City - Susi Safitri; Atira Cesare Mutia (Green Publisher Indonesia, 2022)
China ETS is a system that is implemented in 7 regions in China which called pilot areas, including Shanghai, Beijing, Tianjin, Chongqing, Hubei, Guangdong and Shenzhen, which aiming at reducing GHG emissions or, more specifically, CO2 gas by limiting the production of carbon gas from each emitter (cap) the difference between the emission level and the value of the cap is called a trade (trade). By using panel data and Linear Regression we analyze the impact of China-ETS policy on China Economic growth (GDP) while at the same time analyze the carbon price trend which is one of the factor of the ETS system succeed. The result showing that ETS policy effectively impacts on reducing carbon emission, and there have corelation between carbon price and the carbon amount, Lastly, using ARIMA model on forecasting the carbon amount within 10 years.